Assessment of the usefulness of Neurodevelopmental Centered Care (NCC) in relation to the knowledge and professional experience in Neonatal Intensive Care (NICU) of nurses in a public hospital in the city of Rosario - Bobillo, Rosa Inés (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Prematurity is a well-known problem and a leading cause of newborn deaths. Premature newborns (PTNB) have criteria for admission to Neonatal Intensive Care Units (NICU) for care and survival with a series of neurodevelopmental risks. The aim of this study was to determine the assessment of the usefulness of Neurodevelopmental Centered Care (NCC) in relation to professional knowledge and experience in Neonatal Intensive Care Units (NICU) of nurses in a public hospital in the city of Rosario. A non-experimental, descriptive, qualitative-quantitative, cross-sectional study was carried out on the total population of nurses (25) working in the NICU. The data collection technique was the survey and a self-administered questionnaire was used with 12 items that accounted for the different indicators of the variables. The degree of the respondents showed some parity between undergraduate and undergraduate academic degree; and specific training in NCC -updated to the last year- represented a little more than a third of the population. The nurses' self-perception of their knowledge and experience to perform in the NICU was predominantly intermediate - 84% and 72% respectively. The mean usefulness assessment of 7 activities of the NCC in relation to the evolution and prognosis of the PTNB in the NICU had levels compatible with the range of maximum possible assessment (between value=5 and value=6): impact of stress prevention 5.80; family participation, noise control and pain prevention 5.76; care of the PTNB's posture 5.60; care of maneuvers and contact 5.52; and mother/parent kangaroo method 5.44. It is concluded that the valuation of usefulness of CCN in this population has been very high and no correlation is seen with the academic degree, the training present in CNN and the different levels of self-perceived knowledge and experience in the NICU